Effect of graduated elastic compression stockings on leg symptoms and signs during exercise in patients with deep venous thrombosis: a randomized cross-over trial - Kahn, S.R.; Azoulay, L.; Hirsch, A.; Haber, M.; Strulovitch, C.; Shrier, I. (Journal of thrombosis and haemostasis, 2003)
Graduated elastic compression stockings (ECS) are often prescribed after deep venous thrombosis (DVT) to alleviate acute symptoms and to prevent and treat post-thrombotic syndrome (PTS). In patients with DVT, leg symptoms tend to worsen with exercise. The effects of ECS use during exercise have not been studied. Objectives were to determine whether ECS improve symptoms and signs and increase exercise capacity when worn during treadmill exercise by patients with prior DVT, with or without PTS. The methods employed a randomized cross-over trial. We recruited subjects who had a first episode of unilateral DVT at least 1 year earlier and categorized them as having, or not having, the PTS using a validated scale. Subjects underwent two identical treadmill exercise sessions at least 1 week apart, and were randomly assigned to wear knee-length 30 mmHg ECS on the affected leg during one of the two sessions. Venous symptoms, leg volume, leg circumference and calf muscle flexibility were measured in the affected leg before and after both exercise sessions. Subjects achieved similar percentage maximum predicted heart rates during both sessions. Comparing the ECS to no ECS session, there were no significant differences in treadmill time (21.2 vs. 21.2 min, P = 0.94), gain in leg volume (71 vs. 73 mL, P = 0.83), or change in soleus or gastrocnemius flexibility, whether or not PTS was present. Symptoms in general worsened slightly with exercise regardless of whether or not ECS were worn and did not differ according to PTS status. Per-subject analysis showed that use of ECS resulted in global improvement of symptoms in 25% of subjects, global worsening in 33% of subjects, and had no or inconsistent effects in 42% of subjects. Whether or not PTS was present, the use of ECS during exercise by patients with prior DVT did not improve symptoms and signs during exercise or increase exercise capacity.